Information Retrieval System of the Tree by Using QR Code Technology - Suntornmeth, Pakorn; Pisjan, Panupong; Bualek, Wutthichai (RMUTL Journal of Business Administration and Liberal Arts, 2017)
This research, to develop a system to search the tree with QR codes within the Rajamangala University of Technology Lanna Nan for the convenience of students and the community to find information and to study the user’s satisfaction, the system that brought the trial. The research consists of a method. To collect information such as number of 100 plants fruit trees and perennials from splitting into 3 areas 1) Science Zone 2) Puddharaksa Zone and 3) Agricultural Zone. Development web site for information handling and displaying data with Google maps. Users can search information by scanning through a Mobile Smartphone. Results from the evaluation found that the system users can search the tree, (4.31), which can be utilized in the following botany next.